Microstructured Liquid Metal‐Based Embedded‐Type Sensor Array for Curved Pressure Mapping - Haoyu Li; Chengjun Zhang; Hongyu Xu; Qing Yang; Zexiang Luo; Cheng Li; Lin Kai; Yizhao Meng; Jialiang Zhang; Jie Liang; Feng Chen (Advanced Science)
Abstract Human hands can envelop the surface of an object and recognize its shape through touch. However, existing stretchable haptic sensors exhibit limited flexibility and stability to detect pressure during deformation, while also solely achieving recognition of planar objects. Inspired by the structure of skin tissue, an embedded construction‐enabled liquid metal‐based e‐skin composed of a liquid metal microstructured electrode (LM‐ME) array is fabricated for curved pressure mapping. The embedded LM‐ME‐based sensor elements are fabricated by using femtosecond laser‐induced micro/nanostructures and water/hydrogel assisted patterning method, which enables high sensitivity (7.42 kPa−1 in the range of 0–0.1 kPa) and high stability through an interlinked support isolation structure for the sensor units. The sensor array with a high interfacial toughness of 1328 J m−2 can maintain pressure sensation under bending and stretching conditions. Additionally, the embedded construction and laser‐induced bumps effectively reduce crosstalk from 58 to 7.8% compared to conventional flexible sensors with shared surfaces. The stretchable and mechanically stable sensor arrays possess shape‐adaptability that enables pressure mapping on non‐flat surfaces, which has great potential for object recognition in robotic skins and human‐computer interaction.